Does Extended Intraoperative Peritoneal Lavage Really Bring Benefit on Patients With Gastric Cancer? A Meta-Analysis of Published Clinical Trials - Tao, Wei; Liu, Xiao-Yu; Cheng, Yu-Xi; Kang, Bing; Zhang, Hua; Yuan, Chao; Zhang, Bin; Peng, Dong (Frontiers in Oncology, 2021)
Purpose: The purpose of the current meta-analysis is to analyze whether extended intraoperative peritoneal lavage (EIPL) can bring benefit on short-term outcomes or survival for patients undergoing curative gastrectomy for gastric cancer. Methods: The PubMed, Embase and Cochrane Library databases were searched from inception to May 3, 2021 to find eligible studies. Postoperative complications, overall survival (OS), disease free survival (DFS) and peritoneal recurrence free survival (PRFS) were compared between EIPL group and No EIPL group. Results: A total of five randomized controlled trials with 1790 patients were included in the current meta-analysis. No difference was found in baseline information (p>0.05). After pooling up the data of overall postoperative complications, no significant difference was found between EIPL group and No EIPL group (OR=0.88, 95% CI=0.51 to 1.53, P=0.65). Furthermore, there was no significant difference between EIPL group and No EIPL group in terms of OS (HR=0.77, 95% CI=0.36 to 1.64, P=0.49), DFS (HR=0.97, 95% CI=0.71 to 1.33, P=0.87) and PRFS (HR=1.03, 95% CI=0.74 to 1.43, P=0.86). In terms of subgroup analysis of OS, no significant difference was found as well (HR=1.05, 95% CI=0.82 to 1.34, P=0.69). Conclusions: EIPL did not bring benefit in terms of short-term outcomes or survival. Therefore, EIPL is not recommended for patients undergoing curative gastrectomy for gastric cancer.